Iron and Steel Division - Rate of Reduction of an Oxide Sphere in a Stream of Reducing Gas - Hillary W. St. Clair (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
An equation is derived for the rote of reaction of a sphere of metal oxide in a restricted enclosure through which a reducing gas is flowing. The equation takes into consideration the reaction rate coefficient, transport through the gas and through the porous shell of reduced oxide, the rate of gas flow, THIS paper describes a mathematical study of the chemical and physical processes that determine the rate of reduction of solid metal oxide with a reducing gas. The study was a part of a theoretical study leading to the development of a mathematical model for the simulation of the thermochemical behavior of the iron blast furnace. An essential feature of such and the volume of- space surrounding the sphere available for gas flow. The equation is applied to experimental data on vote of reduction of iron oxide in hydrogen. The equation serves as a model for predicting the course of reduction of a particle of. metal oxide in a shaft furnace. a model is an adequate mathematical relationship defining the rate of reaction in terms of all the important chemical and physical phenomena that affect the rate of reaction. This includes not only the reaction rate coefficients, equilibrium ratios, gas composition, and temperature, but also the relevant physical properties of the oxide, rate of gas flow, and relative volumes occupied by gas and solid. In many previous experimental studies of the rate of reduction of oxides by hydrogen or carbon monoxide, the rate of reduction was assumed to be controlled primarily by the chemical reaction at the